Pig feeding practices of backyard pig farmers in Imphal, Manipur - Lenshi T; Rajaganapathy V; Mandal PK; Ganesan R; Venugopal S; R Raghy; Sreekumar D (The Indian Veterinary Journal, 2025)
A study was conducted to assess the feeding management of pigs practiced by backyard pig farmers in Imphal region of Manipur. A total of 150 pig farmers were selected as respondents. It was found that all the pigs in the region were stall fed with locally available feed ingredients which were mostly home grown. A few of the respondents provided calcium, vitamins and mineral supplements to the pigs. Pigs were fed in groups and feeding was done twice a day. No respondents provided separate drinking water; the feed was mixed with water and fed.